1989
DOI: 10.1073/pnas.86.18.6944
|View full text |Cite
|
Sign up to set email alerts
|

Melittin binding causes a large calcium-dependent conformational change in calmodulin.

Abstract: The interaction between calmodulin and its target protein is a key step in many calcium-regulated cellular functions. Melittin binds tightly to calmoduiln in the presence of calcium and is a competitive inhibitor of codulin function. Using melittin as a model for the target peptide of calmodulin, we have found a large Ca2+-dependent conformational change of almoulin in solution induced by peptide binding. Mg+ does not substitute for Ca2+ in producing the conformation change. Small-angle x-ray scattering has sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
116
0
2

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(135 citation statements)
references
References 27 publications
17
116
0
2
Order By: Relevance
“…Fluorescence and circular dichroism spectroscopy have revealed that in the presence of calcium, both calmodulin and melittin undergo significant structural changes, particularly in the vicinity of tyrosine residues 99 and 138 in calmodulin and at tryptophan 19 in melittin [9]. Small angle X-ray scattering has also identified significant structural changes in calmodulin with its transformation from a dumbbell to globular conformation upon its binding to melittin [13]. Similar conclusions have been drawn from limited proteolysis experiments followed by mass spectrometric analysis [16].…”
mentioning
confidence: 54%
“…Fluorescence and circular dichroism spectroscopy have revealed that in the presence of calcium, both calmodulin and melittin undergo significant structural changes, particularly in the vicinity of tyrosine residues 99 and 138 in calmodulin and at tryptophan 19 in melittin [9]. Small angle X-ray scattering has also identified significant structural changes in calmodulin with its transformation from a dumbbell to globular conformation upon its binding to melittin [13]. Similar conclusions have been drawn from limited proteolysis experiments followed by mass spectrometric analysis [16].…”
mentioning
confidence: 54%
“…3F-H). When we examined melittin, a peptidic inhibitor of CaM from bee venom (18), the combined treatment with melittin/cisplatin showed relative increases in the G 2 -M population (Fig. 4I).…”
Section: Cam Inhibitors Show Similar Activity To Cbp501mentioning
confidence: 99%
“…The proteins are dissolved in the buffer solution with 10 mM Tris (pH 7.4), 10 mM NaCN. Each plot was obtained by the extrapolation to zero protein concentration of the data for four different protein concentrations (23). For clarity, each plot is shifted on the ln(I(Q)) axis.…”
Section: Figmentioning
confidence: 99%
“…The scattering curve at infinite dilution was obtained from a series of scattering data with different protein concentrations (23). X-ray scattering intensities at the small angle region are given as the equation,…”
mentioning
confidence: 99%